Agreement between body weight perception and body weight status among late adolescents in Kuantan, Malaysia - Jamani, Nurjasmine Aida; Said, Abdul Hadi; Abd. Aziz, Karimah Hanim; Abd Rahman, Mohd Aizuddin (Kulliyyah of Medicine, International Islamic University Malaysia, 2020)
ABSTRACT Objectives: Body weight perception may determine the practice of proper weight management. The objective of this study was to measure the agreement between body weight perception and actual body weight status and its associated factors among late adolescents in Kuantan, Malaysia. Methods: A cross-sectional study was conducted from April to October 2018 among 479 adolescents aged 17-19 years old from seven institutions of higher learning in Kuantan. Body weight status was described as body mass index (BMI). Weight and height were measured, and BMI was calculated. Validated, self-administered Figure Rating Scale (FRS) questionnaires were used. Agreement between BMI and body weight perception was calculated using Kappa statistics. Logistic regression was employed to examine the association between body weight perception and sociodemographic variables. Results: More than one-third (35.3%) of the respondents misjudged their own body weight. More than one third of the respondents (38.7%) who were underweight, misperceived themselves as having normal weight whilst 31.7% of obese respondents identified themselves as overweight. The agreement between body weight perception and body mass index was moderate (k0.46, p<0.01). Conclusion: Body weight perception was in moderate agreement with actual weight in late adolescents. Accurate body weight perception is an important factor in late adolescent’s weight management behaviour. Hence, health education related to body weight management should be emphasized among this age group.